SERVICE WAITING TIME ANALYSIS AT REGULAR PHARMACY OF MEDIKA ANTAPANI - Prameswari, Santika; Basri, Mursyid Hasan (Journal of Business and Management, 2018)
Abstract. The services of the public health should be supported by having a proper system and service in the process of operations management. To have optimal workflow, it is important to have the right setup in business process, the work environment and team members. That is a responsibility of the public health to improve the quality to guarantee for patient satisfaction. One of the public health services is in pharmacy installation. Regular Pharmacy of Medika Antapani is the one of the pharmacies in Bandung that provides and sells healthcare equipment, products, and medicine. Regular Pharmacy wants to improve the quality of services to reduce the service waiting time in the system. According to the research, Regular Pharmacy has a high number of demand in peak hour time and has a problem related to the long duration of patient waitin g time. The staff allocation and activities in the business process will be a consideration to increase the service quality. In this research, the staff allocation will be analyzed using iGrafx Simulation. The first step is analyzed the business process in Regular Pharmacy. Then, process time in each activity is needed to know how long the time of existing condition in Pharmacy Services. The recorded time in each process will be used in the IMR Control chart to make sure the data is in-control by using Minitab. The out of control data in IMR chart will be analyzed in Values Analysis to identify the efficiency issues in each activity. Then, the next process is run the Simulation Analysis to obtain the number of average service waiting time and utilization of resource. The output of this research is to reduce the service waiting time and achieve the better utilization of resources to solve the problem in Regular Pharmacy of Medika Antapani.Keywords: Regular Pharmacy, Pharmacy, Service Waiting Time, Values Analysis, Simulation.